Economic feasibilty of solar powered street lighting system in Somalia - Wa Ays, Mohamed Mahad (2021)
Somalia is one of the rising countries that has suffered from an energy crisis due to high electricity losses, less qualified workers and a lack of productivity. The main objective of this research is to evaluate the technological possibilities and benefits of using solar energy to power streetlights in Via the combination of light emitting diode (LED) lights and photovoltaic cells. The cost of purchasing the equipment and operating a solar powered/LED device is consistent with the cost of running grid-connected street lights using electricity. The aim of the project was on the feasibility of using solar energy to power street lights. The functions of design and simulation was achieved through the assistance of HOMER software, the simulation model provides the monthly electricity provided by grid-connected street lights and solar street lights, as well as the best technically feasible solar energy system that is less net present cost (NPC), system energy cost and higher fraction of renewable energy, providing the lowest COE of $0.295/kWh and the total net present cost (NPC) of US$40,03030. This work focuses on the domestic aspect and offers a feasibility analysis to use solar energy and LED lights to serve this purpose and to alleviate this enormous consumption of energy. Solar-powered LED lights create light with the same luminance as 250-watt sodium bulbs Although the initial cost of installing the solar street light is higher than the conventional street lights, the overall long-term effect is quietly remarkable. A research involving 40 lamps over a distance of 2 km showed that in addition to saving national electricity, solar street lights save 59 percent after 20 years of using solar street lights.